Procedures and Implementation of Distribution of Ulayat Land Rights According to Wesei Wehali Customary Law by Fukun (Head of Tribe) in Umakatahan Village, Central Malaka District, Malacca District - Prisilia Floresta Santji Tae Bria; Sukardan Aloysius; Darius Mauritsius (PT FORMOSA CENDEKIA GLOBAL, 2023)
Based on the results of the research that has been done, it can be concluded (1) In the process of dividing customary land rights according to Wesei Wehali customary law by the fukun (tribal head) in Umakatahan village, Central Malacca sub-district, Malacca district, the fukun or tribal chief provides information to oa'laen to provide invitations to indigenous peoples and village officials, sitting together in traditional houses (tur lia) and performing traditional rituals, and designating shared communal land objects. (2) The Inhibiting Factors in the process of distributing land rights according to wesei wehali customary law by fukun (tribal chiefs) in Umakatahan Village, Central Malacca District, Malacca District, namely the absence of approval or support from tribal members and the absence of tribal chiefs and village officials in the appointment land to be shared